Bullwhip effect mitigation of green supply chain optimization in electronics industry. (10th April 2018) - Zhao, Yuhuan; Cao, Ye; Li, Hao; Wang, Song; Liu, Ya; Li, Yue; Zhang, Yongfeng
Abstract: Technological advancement and rapid demand changes, lead to shorter life period and booming waste of electronic products. Recycling and reusing activities of electronic products has attracted much attention on the optimization of green supply chain (SC). This study employs system dynamics (SD) model to explore the effect of single strategy and combined scenarios on mitigating inventory amplification, i.e., bullwhip effect (BE) in three-echelon SC. Novel scenario simulation is designed to stimulate recovery activities of electronic waste, decrease solid material depletion and promote clean production. Main thread is as follows: establishing SD model in line with practical operation mechanism, testing the robustness of model, emulating the effect of single strategy and combined scenarios on mitigating BE and finally proposing optimal strategies on the optimization of green SC. Results show that positive recovery activities is an optimal solution in green SC among single strategies; simulated scenarios alleviate the BE largely especially the combination of higher recovery ratio and information transparency reinforcement. Initially, the emulated-mapping of this field helps graphically illustrate the potential optimized-directions and stimulate individual recovery behaviors in green SC. Highlights: Disordered electronic reverse logistics in China brought a heavy waste of resources and pollution. Bullwhip effect in green supply chain lead to tremendous inefficiencies. System dynamics was used to explore the combined scenarios of bullwhip effect mitigation. Positive recovery activities proved optimal in green supply chain than other strategies. Combination of higher recovery ratio and information transparency reinforcement mitigated bullwhip effect largely.